2003
DOI: 10.1124/jpet.103.055145
|View full text |Cite
|
Sign up to set email alerts
|

TA-270 [4-Hydroxy-1-methyl-3-octyloxy-7-sinapinoylamino-2(1H)-quinolinone], an Anti-Asthmatic Agent, Inhibits Leukotriene Production Induced by IgE Receptor Stimulation in RBL-2H3 Cells

Abstract: A novel quinolinone derivative, TA-270 [4-hydroxy-1-methyl-3-octyloxy-7-sinapinoylamino-2(1H)-quinolinone], has been shown to inhibit antigen-induced asthmatic responses including the early-phase bronchoconstriction in actively sensitized guinea pigs. Here we characterized the action mechanisms of TA-270 in cellular level in vitro. In RBL-2H3 mast cells sensitized with dinitrophenol (DNP)-specific IgE, the antigen exhibited several mast cell functions, including hexosaminidase release as a marker of degranulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The transformation of cyclopenin and cyclopenol into viridicatin and viridicatol through a decarboxylation/rearrangement process was realized by the White and Smith groups (Scheme 1b). 15 The rearrangement of benzo- [6,7]-1,4-diazepino [5,4-b]oxazole derivatives was reported by Tachikawa (Scheme 1c). 16 The condensation process of diazomethane (Scheme 1d) 17 and its derivatives (Scheme 1e) 18 with isatins was realized by the groups of Undheim, Pellicciari, and Gois.…”
Section: ■ Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The transformation of cyclopenin and cyclopenol into viridicatin and viridicatol through a decarboxylation/rearrangement process was realized by the White and Smith groups (Scheme 1b). 15 The rearrangement of benzo- [6,7]-1,4-diazepino [5,4-b]oxazole derivatives was reported by Tachikawa (Scheme 1c). 16 The condensation process of diazomethane (Scheme 1d) 17 and its derivatives (Scheme 1e) 18 with isatins was realized by the groups of Undheim, Pellicciari, and Gois.…”
Section: ■ Introductionmentioning
confidence: 94%
“…5 Desaubry and co-workers synthesized 3-O-methylviridicatin analogues with improved anti-TNF-α properties. 6 Furthermore, compounds containing the 3-hydroxyquinolin-2-one skeleton have also been intensively studied as pharmaceutical agents such as the antiallergy agent TA-270, 7 selective inhibitors of HIV-1 reverse transcriptase, 8 potent D-amino acid oxidase (DAAO) 9 and mitogen-activated protein (MAP) kinase 10 inhibitors, [ 3 H]glycine binding to rat cortical membranes inhibitors, 11 and maxi-K channel openers with antibacterial activities. 12 However, the synthesis of 3-hydroxy-4-quinolin-2-ones has remained largely unexplored: only a few synthetic strategies have been developed for the construction of the skeleton.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Studies of the action mechanisms of TA 270 in cellular level in vitro revealed that it specifically suppresses the antigeninduced leukotriene production, probably by inhibiting 5-lipoxygenase in inflammatory cells. 19 A naturally occurring quinolinone alkaloid has been recently isolated from the aleurone layer of Oryza satiVa cv Hengjinmi. This compound exhibited moderate antioxidant activity in a DPPH free radical scavenging assay.…”
Section: Introductionmentioning
confidence: 99%
“…This compound was designed as an antioxidant, and further studies showed that it is as well a potent inhibitor of immediate- and late-airway responses, pulmonary inflammatory cell accumulation and, airway hyper-responsiveness, therefore, it may be of therapeutic use for the treatment of bronchial asthma. Studies of the action mechanisms of TA 270 in cellular level in vitro revealed that it specifically suppresses the antigen-induced leukotriene production, probably by inhibiting 5-lipoxygenase in inflammatory cells …”
Section: Introductionmentioning
confidence: 99%
“…Compounds containing the quinoline scaffold in the structural framework are expected to have wide-spectrum biological activity. Among their various applications, [1][2][3] functionalised quinolines are in widespread use as a result of their antimalarial, [4][5][6] anti-inflammatory, 7,8 anti-asthmatic, 9,10 antibacterial 11,12 and anti-hypersensitive activities. 13,14 Transition metal-catalysed cross-coupling has proved to be efficient in forming new C-C bonds.…”
mentioning
confidence: 99%